Psychosocial telemonitoring and teleorientation for older adults in the Social Security (EsSalud) during the first six months of the COVID-19 pandemic in Peru - Romero-Albino, Zoila (2022)
Introduction: The Peruvian Social Security during the COVID-19 pandemic implemented a psychosocial remote care program for older adults in order to improve their quality of life and prevent the development of mental problems. The study: Analysis of secondary data from records generated by teams from the Senior Centers at the national level between May and October 2020, with the aim to describe the experience of implementing Psychosocial telemonitoring and teleorientation for elderly patients during COVID-19 pandemic. Findings: A total of 154 280 follow-ups and 36 492 remote care services were provided to older adults. The main interventions provided were emotional support (75.5%) and social counseling (53.8%). The most recorded moods were calmness and worry. Feelings of worry, stress, sadness, and fear are higher in the reports with COVID-19 compared to those without COVID-19. Conclusion: Psychosocial telemonitoring and teleorientation for older adults can be used as another way to provide comprehensive care in elderly population.